2007
DOI: 10.1017/s1368980007000456
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in 1-year follow-up effect of the Dutch Schoolgruiten Project – promoting fruit and vegetable consumption among primary-school children

Abstract: Objective: To evaluate the effect of a primary school-based intervention providing free fruit and vegetables (F&V), separately for children of Dutch and of nonWestern ethnicity. Setting: Primary schools in two regions (west and east) in The Netherlands. Design and methods: Participating schoolchildren and their parents completed questionnaires at baseline and 1 year later, including questions on usual F&V intake, potential determinants and general demographics. Primary outcomes were the usual fruit intake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 26 publications
3
57
1
Order By: Relevance
“…These results on food consumption reported by the Chilean children were generally similar to previous studies from other countries that have reported on dietary consumption in 8 to 13 year olds, [12][13][14] although children from this study reported a higher frequency of consumption of produce [8,[15][16][17][18] than some of the previous studies and a slightly higher consumption of snacks and sweets [18] than one previous study. Separating out green and nongreen vegetables in the Chile questionnaire might have increased total vegetable consumption reported by the study children.…”
Section: Study Populationsupporting
confidence: 90%
“…These results on food consumption reported by the Chilean children were generally similar to previous studies from other countries that have reported on dietary consumption in 8 to 13 year olds, [12][13][14] although children from this study reported a higher frequency of consumption of produce [8,[15][16][17][18] than some of the previous studies and a slightly higher consumption of snacks and sweets [18] than one previous study. Separating out green and nongreen vegetables in the Chile questionnaire might have increased total vegetable consumption reported by the study children.…”
Section: Study Populationsupporting
confidence: 90%
“…An explanation could be that there were relatively more children with a non-Western ethnicity in the intervention group compared with the control group. Tak et al (1) concluded elsewhere about this project that children with non-Western ethnicity reported higher vegetable consumption than children with Dutch ethnicity. Therefore, we adjusted all analyses for baseline differences to solve this problem.…”
Section: Tablementioning
confidence: 75%
“…The components designed and used in this programme are similar to those used in other multi-component interventions which have been shown to be effective (5,10,14,17,19,22) . However, implementation rate is a vital component in the success of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Process evaluations are used to improve the understanding of successful or unsuccessful health interventions; to identify the key components that make an intervention successful, for boys, girls or both; and to determine which environments/conditions lead to these particular components facilitating a successful outcome (21,22) . Two terms commonly used in process evaluations and applied to the present study are implementation (9,(11)(12)(13)15) , meaning to what extent the intervention or intervention items were used by the intended audience; and appreciation (5,10,16,17,19,23) , a rating of how much the participants liked the intervention or intervention items (22) . However, a vital component of process measures is to identify possible mediating variables.…”
mentioning
confidence: 99%